An Assessment of the Longitudinal Impact of Gender-affirming Care in an Adolescent and Young Adult Transmasculine and Nonbinary Patient Population - Emily Ewing, MA; Gabriela Sendek, MD; Miriam Becker, MS; Edna Montes, MS; RocNeil Nguyen, BA; Rachel Jenkins, BA; Clara Lee, MD; Andrew Richardson, MS; Bixby Marino-Kibbee, MSW; David Inwards-Breland, MD; Amanda Gosman, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Gender-affirming care (GAC) during adolescence is associated with decreased adverse gender dysphoria–related outcomes and steadily improved psychological functioning into young adulthood. This single-institution, longitudinal study examined the impact of GAC on various treatment outcomes for transgender and nonbinary adolescents and young adults. Participants included 110 transmasculine and nonbinary adolescents and young adults who were referred for gender-affirming top surgery through the Center for Gender-Affirming Care and Plastic Surgery multidisciplinary clinic at Rady Children’s Hospital, San Diego. Methods:. Outcomes were assessed via the Patient Health Questionnaire-2, chest and gender dysphoria scales, and surgical satisfaction scales, which were administered at various time points throughout treatment. Multilevel modeling was used to evaluate the impact of GAC on depressive symptoms, chest and gender dysphoria, and surgical satisfaction over time. Results:. Significant reductions were observed in patient-reported depressive symptoms, gender dysphoria, and chest dysphoria before and after surgery. On average, survey results indicated that patients reported positive perceptions of their surgical experience, were satisfied with their surgical outcome, and had a positive recovery experience. Conclusions:. Results suggest that GAC appears to have a measurable and beneficial impact on patients’ mental health.